Chromosome organisation during ageing and senescence. (June 2016) - Chandra, Tamir; Kirschner, Kristina
Highlights: Acute and chronic cellular stress models show distinct nuclear phenotypes. Heterochromatin relaxes in acute and chronic cellular stress. Heterochromatin relaxation causes the activation of repeat elements. Mechanisms specific to acute stress might block repeat activation. Abstract : Acute cellular stress caused by oncogene activation or high levels of DNA damage can engage a tumour suppressive response, which can lead to cellular senescence. Chronic cellular stress evoked by low levels of DNA damage or telomere erosion is involved in the ageing process. In oncogene induced senescence in fibroblasts, a dramatic rearrangement of heterochromatin into foci and accumulation of constitutive heterochromatin is well documented. In contrast, a loss of heterochromatin has been described in replicative senescence and premature ageing syndromes. The distinct nuclear phenotypes that accompany the stress response highlight the differences between acute and chronic stress models, and this review will address the differences and similarities between these models with a focus on chromosome organisation and heterochromatin.